The Fiscal Effect of Immigration: Reducing Bias in Influential Estimates - Michael A. Clemens (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2021)
Immigration policy can have important net fiscal effects that vary by immigrants' skill level. But mainstream methods to estimate these effects are problematic. Methods based on cash-flow accounting offer precision at the cost of bias; methods based on general equilibrium modelling address bias with limited precision and transparency. A simple adjustment greatly reduces bias in the most influential and precise estimates: conservatively accounting for capital taxes paid by the employers of immigrant labor. The adjustment is required by firms' profit-maximizing behavior, unconnected to general equilibrium effects. Adjusted estimates of the positive net fiscal impact of average recent U.S. immigrants rise by a factor of 3.2, with a much shallower education gradient. They are positive even for an average recent immigrant with less than high school education, whose presence causes a present-value subsidy of at least 128,000 to all other taxpayers collectively.
Keywords: F22; H68; J61; 330